2003
DOI: 10.1039/b308577e
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cleavage of the naphthylmethyl–oxygen bond in higher triplet excited states

Abstract: Rapid cleavage of the naphthylmethyl-oxygen bond of 1- and 2-[(4-benzoylphenoxy)methyl]naphthalenes in higher triplet excited states occurred within a laser flash of 5 ns to give 1- and 2-naphthylmethyl radicals with formation quantum yields of 0.042 +/- 0.004 and 0.020 +/- 0.002, respectively, during two-colour two-laser flash photolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 10 publications
4
47
0
Order By: Relevance
“…No recovery of the T 1 state after the second laser flash indicated that decomposition of the T 1 state upon second laser photolysis occurred in the T n state. [8,9,11] Based on the transient absorption measurement, the decomposition is assigned to the CÀO-bond cleavage. [8,9,11] In the case of a NpCO-OPh, with a decrease of the absorption intensity of a NpCO-OPh(T 1 ), absorption bands of phenoxyl radical (PhOC) at 362 and 398 nm were observed (Figure 3a, solid line).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No recovery of the T 1 state after the second laser flash indicated that decomposition of the T 1 state upon second laser photolysis occurred in the T n state. [8,9,11] Based on the transient absorption measurement, the decomposition is assigned to the CÀO-bond cleavage. [8,9,11] In the case of a NpCO-OPh, with a decrease of the absorption intensity of a NpCO-OPh(T 1 ), absorption bands of phenoxyl radical (PhOC) at 362 and 398 nm were observed (Figure 3a, solid line).…”
Section: Resultsmentioning
confidence: 99%
“…[8,9,11] Based on the transient absorption measurement, the decomposition is assigned to the CÀO-bond cleavage. [8,9,11] In the case of a NpCO-OPh, with a decrease of the absorption intensity of a NpCO-OPh(T 1 ), absorption bands of phenoxyl radical (PhOC) at 362 and 398 nm were observed (Figure 3a, solid line). [17][18][19] Absorption bands of the counter radical, a-naphthoyl radical ( (Figure 3b, inset).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-color irradiation also offers spatial control of the reaction at the focal point of the lasers. [29][30][31][32][33] The photosensitizer NDI used in this preliminary experiment is not adequate for practical as since the charge-separation yield is small (about 2 %) owing to the fast charge recombination from the contact radical ion pair. [27,34] Therefore, a second laser exerts its effect only on NDIC À generated by occasional escape from the charge recombination by hole transfer.…”
Section: Methodsmentioning
confidence: 99%
“…This strategy has the advantage that the intensity of the 355-nm pulses in the first step can be kept low, and a high DNA damaging efficiency can be attained by applying the second laser pulse at a longer wavelength with a greater depth of tissue penetration due to reduced scattering and minimal absorption from nonpharmacological chromophores in the tissue. Twocolor irradiation also offers spatial control of the reaction at the focal point of the lasers [56][57][58][59][60]. The photosensitizer NDI used in this preliminary experiment is not adequate for practical use since the charge-separation yield is small at about 2 % owing to the fast charge recombination from the contact radical ion pair [18,39].…”
Section: Figmentioning
confidence: 99%